Who weans with commodity price shocks? Rice prices and breastfeeding in the Philippines - Michael R.M. Abrigo (Philippine Institute for Development Studies (PIDS), 2016)
Commodity market fluctuations have been linked with a number of adult outcomes. Recent evidence on the lasting impact of early life conditions, however, suggests that the effects on children may be important as well. Using large spatio-temporal variations in rice prices in the Philippines as a natural experiment, the study estimates the effect of increasing food prices on parental behavior regarding an inexpensive yet time-intensive child investment: breastmilk feeding. It documents a countercyclical relationship between breastfeeding duration and rice prices, which may be a consequence of poorer health and induced labor force participation among mothers. Results highlight that even food producers may not be insulated against food price inflation.
Keywords: I18; J13; Q02; 330; Food prices; Breastfeeding; Child investments